Upaya Lembaga Swadaya Masyarakat Yayasan Kepedulian untuk Anak (Yayasan KAKAK) dalam Melindungi Hak atas Pelindungan Terhadap Anak Korban Kekerasan Seksual di Kota Surakarta: UPAYA LEMBAGA SWADAYA MASYARAKAT YAYASAN KEPEDULIAN UNTUK ANAK (YAYASAN KAKAK) DALAM MELINDUNGI HAK ATAS PELINDUNGAN TERHADAP ANAK KORBAN KEKERASAN SEKSUAL DI KOTA SURAKARTA - Hima Yuliana Zahroh; Hartanto, Rima Vien Permata; Winarno, Winarno (Prodi PPKn Universitas Slamet Riyadi, 2024)
ABSTRACT This study aims to analyze the efforts of the non-governmental organization Kakak Foundation and to describe the inhibiting factors of the efforts of the non-governmental organization Yayasan Kepedulian untuk Anak (Kakak Foundation) in protecting the right to protection of child victims of sexual violence in Surakarta City. This research is a descriptive qualitative research. With data sources obtained from informants, documents, and places of events. The sampling technique was used with purposive sampling. Data collection techniques used interviews, observation, and documentation studies. The data validity test uses triangulation of methods and data sources. While data analysis techniques with data collection, data reduction, data presentation, and conclusion drawing. The results of this study are 1) Efforts of Non-Governmental Organization Kakak Foundation in protecting the right to protection of child victims of sexual violence in Surakarta City from the elaboration of laws and regulations related to the right to protection of child victims of sexual violence consists of 7 rights, namely (a) the right to the provision of information on protection rights and facilities, (b) the right to provide access to information on the implementation of protection, (c) the right to protection from the threat or violence of the perpetrator and other parties and the recurrence of violence, (d) the right to protection of identity confidentiality, (e) the right to protection from the attitude and behavior of law enforcement officers who humiliate victims, (f) the right to protection from loss of employment, job transfer, education, or political access, and, (g) the right to protection of the victim and/or reporter from criminal prosecution or civil lawsuit for the crime of sexual violence that has been reported. 2) The inhibiting factors are (a) difficulty in obtaining information on child victims of sexual violence, (b) pressure and threats made by the perpetrator, (c) the victim's unstable mental and psychological condition, and (d) many considerations for the victim if they have to take legal action. Keywords: Rights, Child Victims of Sexual Violence, Foundation